The POSSI Code - A Computer Program for a Two-Dimensional Problem of Soil Structure Interaction-Lined Cavity in a Bilinear Medium Axisymmetric Case. - Matthews,A T; Bleich,H H (1977)
POSSI is a FORTRAN Computer code for computing the response of an axisymmetric soil/structure interaction problem cylindrical (r,z) coordinates. The configuration consists of a lined cylindrical cavity of finite length extending from the surface into a semi-infinite half-space, and loaded internally with a pressure p(z, t) or p(r, t) where applicable. The cavity lining is a thin cylindrical shell with bending stiffness, welded to an axisymmetric circular bottom plate with both bending and extensional motion. A right angle may be maintained at the plate/shell connection. The surrounding material is bilinear, with hysteresis in volumetric response only. (Author)